Pendeteksian Ketinggian Air di Lahan Basah Memakai Teknologi Radio Frequency Identification (RFID) dalam Upaya Memonitor Ketersediaan Air untuk Persawahan di Area Pasang Surut - Irwin Bizzy (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Indonesia has quite a lot of scattered wetlands in Sumatra, Borneo, and Papua so that it takes the right technology development to optimize the use of agricultural wetlands for welfare. Tidal wetlands will determine the success of the harvest of food crops, sometimes the tide caused the death of crops due to the amount of water beyond the plant it self or otherwise drought. A technology Radio Frequency Identificationor RFID is one way to monitor water levels in wetlands remotely using radiowaves. This technology is an automate detection system with information technology and communication devices without cables consisting of RFID, reader signal, and a computer. Reader will send signals to RFID to identify or communicate to move the data and will be responded to by the software installed in the computer. The software will immediately respond to convert the data that informed and also to filter or delete data that is not desirable. The data on wetland water level can be monitored as a function of time and recorded in the computer, making it easier to collect these data. These data will be used in planning for the time of planting and crops adapted to the conditions of water throughout the year. It is expected that increase in crop yields in the wetland have ups and downs throughout the year with the availability of accurate data on the water level every season throughout the year